The Mechanism of Ethylene Signaling Induced by Endophytic Fungus Gilmaniella sp. AL12 Mediating Sesquiterpenoids Biosynthesis in Atractylodes lancea - Yuan, Jie (Front Plant Sci, 2016)
Ethylene, the first known gaseous phytohormone, is involved in plant growth, development as well as responses to environmental signals. However, limited information is available on the role of ethylene in endophytic fungi induced secondary metabolites biosynthesis. Atractylodes lancea is a traditional Chinese herb, and its quality depends on the main active compounds sesquiterpenoids. This work showed that the endophytic fungus Gilmaniella sp. AL12 induced ethylene production in Atractylodes lancea. Pre-treatment of plantlets with ethylene inhibiter aminooxyacetic acid (AOA) suppressed endophytic fungi induced accumulation of ethylene and sesquiterpenoids. Plantlets were further treated with AOA, salicylic acid (SA) biosynthesis inhibitor paclobutrazol (PAC), jasmonic acid inhibitor ibuprofen (IBU), hydrogen peroxide (H(2)O(2)) scavenger catalase (CAT), nitric oxide (NO)-specific scavenger 2-(4-Carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide potassium salt (cPTIO). With endophytic fungi inoculation, IBU or PAC did not inhibit ethylene production, and JA and SA generation were suppressed by AOA, showing that ethylene may act as an upstream signal of JA and SA pathway. With endophytic fungi inoculation, CAT or cPTIO suppressed ethylene production, and H(2)O(2) or NO generation was not affected by 1-aminocyclopropane-1-carboxylic acid (ACC), showing that ethylene may act as a downstream signal of H(2)O(2) and NO pathway. Then, plantlets were treated with ethylene donor ACC, JA, SA, H(2)O(2), NO donor sodium nitroprusside (SNP). Exogenous ACC could trigger JA and SA generation, whereas exogenous JA or SA did not affect ethylene production, and the induced sesquiterpenoids accumulation triggered by ACC was partly suppressed by IBU and PAC, showing that ethylene acted as an upstream signal of JA and SA pathway. Exogenous ACC did not affect H(2)O(2) or NO generation, whereas exogenous H(2)O(2) and SNP induced ethylene production, and the induced sesquiterpenoids accumulation triggered by SNP or H(2)O(2) was partly suppressed by ACC, showing that ethylene acted as a downstream signal of NO and H(2)O(2) pathway. Taken together, this study demonstrated that ethylene is an upstream signal of JA and SA, and a downstream signal of NO and H(2)O(2) signaling pathways, and acts as an important signal mediating sesquiterpenoids biosynthesis of Atractylodes lancea induced by the endophytic fungus.